Intrapartum use of zidovudine in a large cohort of pregnant women living with HIV in Italy. Issue 5 (November 2022) - Taramasso, Lucia; Bovis, Francesca; Di Biagio, Antonio; Mignone, Federica; Giaquinto, Carlo; Tagliabue, Claudia; Giacomet, Vania; Genovese, Orazio; Chiappini, Elena; Salomè, Serena; Badolato, Raffaele; Carloni, Ines; et al.
Highlights: Peripartum HIV-RNA is the strongest factor influencing vertical transmission of HIV. When HIV-RNA is <50 copies/mL, ART discontinuation is the strongest risk factor. Intrapartum ZDV has no effect on transmission in women with HIV RNA <50 copies/mL. The administration of unnecessary zidovudine may be perceived as a stigma. Study of the U=U concept in mother-child couple could help fight stigma. Abstract: Background: Intravenous administration of zidovudine (ZDV) during labour is a key step for vertical HIV transmission (VT) prevention, but there is no evidence of benefit when maternal HIV-RNA at delivery is <50 copies/mL. The aim of this study is evaluating the appropriateness of intrapartum ZDV use in Italy. Methods: Observational study including mother-infant pairs with perinatal HIV exposure during 2002-2019, enrolled in the Italian Register for HIV Infection in Children. Univariable and multivariable logistic regression were used to evaluate factors associated with VT. Results: A total of 3, 861 infants, born from 3, 791 pregnancies were included. The frequency of ZDV use was 79.9%, 92.1%, 93.7% and 92.8% when HIV-RNA was not available, ≥400 copies, between 50 and 399 copies, and <50 copies/mL. Thirty-three out of 3861 (0.85%) infants were subsequently diagnosed with HIV, 25/3861 (0.6%) of them born to mothers receiving intrapartum ZDV, and 31 (93.9%) to mothers with HIV-RNA ≥50 copies/mL or not available. In women with HIV-RNA < 50 copies/mL, ART discontinuation during pregnancy was the strongest risk factor for VT (odds ratio, OR, 23.1, 95%CI 2.4-219.3), while a higher gestational age (OR 0.6, 95%CI 0.4-0.8) and PEP administration to the newborn (aOR 0.004, 95%CI <0.0001-0.4) were protective factors. Intrapartum ZDV administration did not influence the final outcome in this group. Conclusions: In ART era, more transmission events may occur in utero, limiting value of intrapartum ZDV, particularly for women with suppressed HIV-RNA load. More attention to the HIV-RNA testing of mothers before delivery may avoid unnecessary ZDV use.